Analisis Kepailitan PT Istaka Karya Sebagai Badan Usaha Milik Negara - Ledy Wila Yustini; Serlika Aprita; M. Andres Arta Al Fajri (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
Overlapping regulations regarding SOE bankruptcy have resulted in inconsistencies in Judges' decisions in deciding SOE bankruptcy cases. The bankruptcy case that befell PT Istaka Karya (Persero) was due to debts in the form of promissory notes that had not been paid. In the Cassation Decision, PT Istaka was declared bankrupt, but in the Judicial Review Decision, PT Istaka's bankruptcy statement was canceled. The writing of this law is intended to find out the legal consequences of canceling a bankruptcy statement at a State-Owned Enterprise (Persero) for paying off its debts to creditors and to find out the reasons for the Supreme Court Review Decision canceling the Cassation Decision in the bankruptcy case of PT. Istaka Karya (Persero). Based on the results of the study, the cancellation of a bankruptcy statement at BUMN (Persero) does not eliminate the obligation of BUMN (Persero) to pay its debts to creditors. Debtor debt problems to creditors after the cancellation of the bankruptcy decision were resolved in a way outside the bankruptcy institution which was agreed upon by both parties. The reasons for the Supreme Court Review decision annulled the Cassation Decision in the bankruptcy case of PT. Istaka is the elimination of the element "there is one debt that has matured and can be collected" in the submission of PT Istaka's bankruptcy application so that PT Istaka's bankruptcy statement was canceled by the Panel of Judicial Review Judges.Keywords: Legal Consequences; Cancellation; Bankruptcy; BUMN (Persero) AbstrakPengaturan mengenai kepailitan BUMN yang masih tumpang-tindih mengakibatkan inkonsistensi pada putusan Hakim dalam memutus perkara kepailitan BUMN. Kasus kepailitan yang menimpa PT Istaka Karya (Persero) disebabkan karena adanya utang berupa surat sanggup yang belum terbayar. Pada Putusan Kasasi PT Istaka dinyatakan pailit, namun pada Putusan Peninjauan Kembali Pernyataan pailit PT Istaka dibatalkan. Penulisan hukum ini dimaksudkan untuk mengetahui akibat hukum pembatalan pernyataan pailit pada Badan usaha Milik Negara (Persero) terhadap pelunasan hutang-hutangnya kepada para Kreditur serta untuk mengetahui Alasan Putusan Peninjauan Kembali Mahkamah Agung membatalkan Putusan Kasasi dalam perkara kepailitan PT. Istaka Karya (Persero). Berdasarkan hasil penelitian, pembatalan pernyataan pailit pada BUMN (Persero) tidak menghapuskan kewajiban BUMN (Persero) dalam membayar utang-utangnya kepada para Kreditor. Permasalahan utang Debitor kepada para Kreditor pasca dibatalkanya putusan pailit diselesaikan dengan cara diluar lembaga kepailitan yang disepatkati oleh kedua belah pihak. Alasan putusan Peninjauan Kembali Mahkamah Agung membatalkan Putusan Kasasi dalam perkara kepailitan PT. Istaka adalah hapusnya unsur “adanya satu utang yang telah jatuh waktu dan dapat ditagih” dalam pengajuan permohonan pailit PT Istaka sehingga pernyataan pailit PT Istaka dibatalkan oleh Majelis Hakim Peninjauan Kembali. Kata Kunci: Akibat Hukum; Pembatalan; Pailit; BUMN (Persero)